Political Participation: A Developmental Perspective - عباس مراره , د. علي (Dirasat in Economics and Business, 2004)
the collapse of the soviet union and the disintegration of the socialist camp have put a decisive end to the dichotomy of the world tp bf divided into two camps: capitalist and socialist yet it has not brought to an end another dichotomy by whivh the world had divided into bloks -advanced and under developed